2007
DOI: 10.1175/2007jcli1526.1
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Radiosonde Wind Data in Representing Climatological Variations of Tropospheric Temperature and Baroclinicity in the Western Tropical Pacific

Abstract: The utility of the thermal wind equation (TWE) in relating tropospheric (850-300 hPa) wind and temperature on climatological time scales is assessed, based on data from 59 radiosonde stations in the western tropical Pacific during 1979Pacific during -2004. Observed long-term mean and seasonal variations closely obey geostrophic balance; incorporating additional (ageostrophic) terms yields negligible improvement. The authors conclude that observed winds offer a useful constraint on the horizontal structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…We should also consider additional independent evidence (either physical or statistical) that might be placed on the estimation of break points. One example may be the thermal wind relation (Allen and Sherwood 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We should also consider additional independent evidence (either physical or statistical) that might be placed on the estimation of break points. One example may be the thermal wind relation (Allen and Sherwood 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Mears et al (2006) suspect that especially the lower stratospheric time series from radiosondes are biased and Sherwood et al (2005) and Randel and Wu (2006) have described pervasive daytime biases in the tropics. Allen and Sherwood (2007) have further shown that the apparent cooling in tropical radiosonde temperatures is not consistent with wind shear changes in this region. However, all this evidence has been fragmentary so far and the radiosonde biases have yet to be removed in a comprehensive manner.…”
Section: Introductionmentioning
confidence: 89%
“…Here we briefly discuss further tests of this method and present the results of applying it to the global radiosonde network. Another advance on previous work is the use of observed wind shear fluctuations to help identify natural temperature variability, as recommended by Allen and Sherwood (2007).…”
Section: Introductionmentioning
confidence: 99%